2015
DOI: 10.11138/mltj/2015.5.2.099
|View full text |Cite
|
Sign up to set email alerts
|

The molecular systemic and local effects of intratendinous injection of Platelet Rich Plasma in tendinosis: preliminary results on a rat model with ELISA method

Abstract: showed no significant modification of their biological markers at D7, D13, D18 and D25 (p>0.22). Comparison of immunological sample tendon markers of PRPT+, PST+ and T+ groups also showed no significant modification of markers at D7, D13, D18 and D25 (p>0.16) considering each biological marker and also all subgroups confounded. Conclusion: our study strongly suggests that a single intratendinous US-guided injection of PRP in Achilles and patellar T+ doesn't increase biological markers such as growth factors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As the animal model for the patellar tendinopathy, it was suggested that a model prepared using a repetitive running exercise on a rodent treadmill machine pathophysiologically reproduced well an actual tendinopathy compared to the collagenase-induced model, since there was no inflammation reaction in/around the tendon in actual tendinopathy although the inflammation was observed in/around the tendon in the collagenase-induced tendinopathy and the clinical tendinopathy was pathogenetically induced with the over-use and/or over-load stress like a repetitive running exercise for a long distance [18][19][20][21] . The previous basic researches described above and also the current animal study 22 were performed using the collagenase-induced model and there was no examination, which examined the therapeutic effect of PRP for the tendinopathy in an animal model prepared using a repetitive running exercise on a rodent treadmill machine to our knowledge at the present. We have experienced to make this animal model and have examined the study using the rat tendinopathy model prepared by a repetitive running exercise 23 .…”
Section: Introductionmentioning
confidence: 99%
“…As the animal model for the patellar tendinopathy, it was suggested that a model prepared using a repetitive running exercise on a rodent treadmill machine pathophysiologically reproduced well an actual tendinopathy compared to the collagenase-induced model, since there was no inflammation reaction in/around the tendon in actual tendinopathy although the inflammation was observed in/around the tendon in the collagenase-induced tendinopathy and the clinical tendinopathy was pathogenetically induced with the over-use and/or over-load stress like a repetitive running exercise for a long distance [18][19][20][21] . The previous basic researches described above and also the current animal study 22 were performed using the collagenase-induced model and there was no examination, which examined the therapeutic effect of PRP for the tendinopathy in an animal model prepared using a repetitive running exercise on a rodent treadmill machine to our knowledge at the present. We have experienced to make this animal model and have examined the study using the rat tendinopathy model prepared by a repetitive running exercise 23 .…”
Section: Introductionmentioning
confidence: 99%